Konsep Sufi Sejati dalam Kitab Utama Tarekat di Indonesia: Studi atas Kitab Al-Risālah Al-Qusyairiyyah - Aly Mashar (KURAS Institute, 2023)
This paper examines one of the most popular Sufism books among Sufism akhlāqī, the al-Risālah al-Qusyairiyyah by Imām al-Qusyairi. More specifically, it is about the concept of True Sufi, or what is often referred to as al-Insān al-Kāmil, according to the great figure of Sufism whose views are widely followed by Hujjatul Islam al-Ghazali, Imām al-Qusyairi. The result of this study is that al-Qusyairi does not clearly explain in his book the concept of 'True Sufi’, but from the many explanations contained in the book, especially in the chapter of Taşawwūf, which contains the definitions of Sufism according to Sufi figures, and also the expression of al-Qusyairi respect for the earlier Sufis found in the introduction to the book, then it can be concluded that the 'True Sufis' according to al-Qusyairi are: have a solid aqidah, practice all the teachings of sharia, always seek to cleanse oneself -both żāhir and bāṭin- from despicable morals and adorn oneself with the morals of the Prophet, always hope to be close to Allah 'taqarrub ilā Allāh’, and be the source of the protector of all beings on earth.